Mechanical Properties and Microstructure Evolution of Cemented Tailings Backfill Under Seepage Pressure - Ke, Yuxian; Shen, Yang; Qing, Chen; Hu, Kaijian; Wang, Shi; Chen, Qiusong; Guan, Huadong (Frontiers in Materials, 2022)
Cemented tailing backfill (CTB) in underground mine inevitably experiences seepage field, which complicates its mechanical behavior. In this study, the mechanical properties and microstructure characteristics of CTB under different seepage water pressures (SWPs) were investigated. The results show that, with the increase in SWP, the mechanical properties of CTB decrease, but the decreasing trend reduces gradually. Higher SWP leads the microstructure of CTB looser and more porous, and the largest proportion of pores initiated and propagated by SWP is micropores, which means the damage in CTB under seepage is mostly caused by micropores. Besides, the mechanical properties of CTB under seepage decrease exponentially with the increase in porosity and present linearly inverse proportional relation to the pore area fractal dimension. Results above indicate that SWP has a significant deterioration effect on the mechanical properties and microstructure of CTB. The research could not only extend the knowledge of mechanical properties and microstructure characteristics of CTB under seepage but also provide a theoretical reference for mechanical index determination and stability analysis of CTB in water-rich underground mines.